The tarsal belt procedure for the correction of ectropion: description and outcome in 42 cases. Issue 12 (3rd July 2014) - Pascali, Michele; Corsi, Andrea; Brinci, Lorenzo; Corsi, Isabella; Cervelli, Valerio
Abstract : Background/aims: Ectropion correction is a challenge in plastic surgery. Correction of the lower lid area, including restoration of the shape and position of lid margin, is the surgical goal. In this study, we describe a new surgical technique, the tarsal belt, for the correction of ectropion and evaluation of the effective outcome and complications of this procedure. Methods: Between January 2008 and January 2012, a total of 42 patients aged between 48 and 75 years (average age 61.5 years) were treated with this technique. This procedure consists in a trans-tarsal mattress non-absorbable suture anchored to the periosteum of the lateral orbital rim, combined with a small wedge excision of a lateral portion of the tarsus close to the lateral canthal tendon. During the same period, 66 patients were treated with the standard lateral tarsal strip technique. Preoperative and postoperative Ectropion Grading Scale (EGS) was recorded to evaluate anatomical improvement. The average follow-up period was 24 months. Results: Rate of success was 100% for involutional and cicatricial ectropions, 90% for lid retraction and 87.5% for paralytic ectropions. Anatomical success according to EGS scale was obtained in 41 patients. Recurrence of ectropion occurred in only one patient 6 months after the first surgery and required a further operation with a larger posterior lamella resection and new tarsal belt suture. Conclusions: The tarsal belt seems to be effective to correct the horizontal and vertical instability of the lid. The suture supports the lower eyelid along the entire tarsal plate length and corrects the outward buckling of the tarsal plate.